2018
DOI: 10.1371/journal.pone.0206689
|View full text |Cite
|
Sign up to set email alerts
|

The biological functions of target genes in pan-cancers and cell lines were predicted by miR-375 microarray data from GEO database and bioinformatics

Abstract: BackgroundMicroRNA is endogenous non-coding small RNA that negative regulate and control gene expression, and increasing evidence links microRNA to oncogenesis and the pathogenesis of cancer. The goal of this study was to explore the potential molecular mechanism of miR-375 in various cancers.MethodsMiR-375 overexpression in different tumor cell lines was probed with microarray data from Gene Expression Omnibus (GEO). The common target genes of miR-375 were obtained by Robust Rank Aggregation (RRA), and identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
1
1
0
Order By: Relevance
“…The next biomarker is cg05713971 near an effective gene called HERPUD1 Antineoplastic activity has been shown to be associated with gene HERPUD1 and further related to human cervical carcinoma according to a recent in vitro experiment ( 52 ). Such gene has also been detected to be regulated by functional microRNA miR-375 and further contributes to HPV-positive cervical cancer, validating our prediction ( 53 ).…”
Section: Discussionsupporting
confidence: 82%
“…The next biomarker is cg05713971 near an effective gene called HERPUD1 Antineoplastic activity has been shown to be associated with gene HERPUD1 and further related to human cervical carcinoma according to a recent in vitro experiment ( 52 ). Such gene has also been detected to be regulated by functional microRNA miR-375 and further contributes to HPV-positive cervical cancer, validating our prediction ( 53 ).…”
Section: Discussionsupporting
confidence: 82%
“…Functional enrichment analysis of target genes in pan-cancer (including MTC) showed specific biological function of miR-375: amino acid biosynthetic, metabolic process and Cysteine and methionine metabolism. In particular, VASN, MAT2B, HERPUD1, TPAPPC6B and TAT were listed as probable gene targets of miR-375 (Zeng, Liang, Lan, Zhu, & Liang, 2018). Other studies identified different subsets of deregulated miRNAs.…”
Section: Bioinformatics Studies Identifying Mirnas In Mtcmentioning
confidence: 99%